Implementasi Pendidikan Religiusitas Berbasis Multikultural di SMA Sint. Corolus Kota Bengkulu - Eva Dewi (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2019)
Law Number: 20 of 2003 concerning the National Education System, states that education is a conscious and planned effort to create an atmosphere of learning and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, morals noble, as well as the skills needed by himself, society, nation and state. Based on preliminary observational data obtained by the author at Sint Carolus Catholic High School in Bengkulu City, the total number of students is 263 people, with 129 male and 134 female students. Meanwhile the number of students based on their religion is 48 Muslim students, 71 Catholic students, 96 Christian students, 46 Buddhist students, 1 student Confucius, and 1 student belief stream.